The Role of the Legal System in Handling Child Abuse and Protection Cases - Pratama, Deo (Siber International Journal of Advanced Law (SIJAL), 2024)
This study examines the role of Indonesia’s legal system in handling cases of child molestation and ensuring the protection of children as victims of sexual violence. Using a normative juridical approach, the research analyzes existing legal provisions, including the Child Protection Act and related regulations, to assess their effectiveness in providing justice and safeguarding children’s rights. The findings reveal that although Indonesia has a comprehensive legal framework, the implementation often faces significant challenges such as limited law enforcement capacity, lack of specialized training for officers, and insufficient rehabilitation services for victims. Moreover, societal stigma and a lack of awareness further hinder optimal legal protection. The study recommends strengthening the capacity of law enforcement, improving rehabilitation facilities, and increasing public awareness to enhance the legal protection of child victims of molestation in Indonesia.